AROMA: real-world global registry of dupilumab for chronic rhinosinusitis with nasal polyps. Issue 4 (28th November 2022) - Siddiqui, Shahid; Bachert, Claus; Chaker, Adam M.; Han, Joseph K.; Hellings, Peter W.; Peters, Anju T.; Heffler, Enrico; Kamat, Siddhesh; Zhang, Haixin; Nash, Scott; Khan, Asif H.; De Prado Gomez, Lucia; et al.
Chronic rhinosinusitis with nasal polyps (CRSwNP) is a predominantly type 2 inflammatory disease of the nasal and paranasal sinuses. Dupilumab is a monoclonal antibody that blocks the shared receptor component for interleukin-4 and interleukin-13, which are key and central drivers of type 2 inflammation. In clinical trials, dupilumab significantly improved objective and patient-reported measures of CRSwNP versus placebo and was well tolerated. Dupilumab is approved in the European Union, USA and Japan as add-on maintenance treatment for adults with inadequately controlled CRSwNP. There exists an important evidence gap between efficacy and effectiveness data for dupilumab in severe CRSwNP. In order to bridge this gap, the AROMA prospective global registry (ClinicalTrials.gov : NCT04959448) was established. AROMA will collect long-term data on the utilisation, effectiveness and safety of dupilumab for CRSwNP treatment in real-world clinical practice. AROMA will enrol approximately 1000 adults starting dupilumab for severe CRSwNP across 120 global sites. Baseline data will include patient demographics, medical/surgical history and presence of type 2 comorbidities. Effectiveness outcome assessments will include objective measures of CRSwNP assessed as part of routine clinical care and various patient-reported questionnaires. Treatment patterns, concomitant medications and long-term safety will also be recorded. Results from AROMA, the first prospective, real-world, global registry to characterise patients with severe CRSwNP starting dupilumab, will provide evidence on the real impact of dupilumab in patients with CRSwNP and complement the data from randomised clinical trials. The registry will also provide evidence on disease progression in patients with CRSwNP, including those with coexisting diseases. AROMA, the first global registry to characterise patients with severe CRSwNP initiating dupilumab, will bridge the key evidence gap between efficacy and real-world effectiveness of dupilumab and generate evidence on long-term progression of severe CRSwNP https://bit.ly/3BEEB8N